Anti-dementia drugs: what is the evidence in advanced stages? - Noémi Daniela Queiroz Nogueira (2022)
Dementia is a major public health concern due to its increasing prevalence, substantial caregiver burden and high financial costs. Currently, the anti-dementia drugs aim only at a symptomatic effect. The subject of prescribing these drugs in advanced stages is a matter of considerable debate, with different countries making distinct recommendations. In this review article, we analyzed the evidence regarding cognitive and functional outcomes, adverse events, health-related costs and caregiver burden in patients with advanced Alzheimer's disease and mixed dementia. We included 35 studies. Most studies are heterogeneous, focus exclusively on Alzheimer's disease, and show small benefits in terms of cognitive and functional scales. The overall evidence seems to suggest a benefit in introducing or maintaining anti-dementia drugs in patients with advanced dementia, but clinical meaningfulness is difficult to ascertain. The issue of costs and caregiver burden is significantly underexplored in this field, but also seems to favor treatment continuation, despite a reduced overall effect. The decision of introducing or withdrawing anti-dementia drugs in advanced stages of dementia should be individualized. Future studies with homogenous designs and outcomes are warranted.